2020
DOI: 10.1186/s12888-020-03009-w
|View full text |Cite
|
Sign up to set email alerts
|

Psychological disturbances of survivors throughout COVID-19 crisis: a qualitative study

Abstract: Background In addition to physical problems, patients with COVID-19 suffer from considerable stress throughout the disease crisis. It is important to address mental health needs and not to ignore the psychological dimension in this group of patients. In this regard, the first practical step is to have a clear understanding of patients’ psychological issues. Therefore, this study aimed to explore the psychological disturbances of COVID-19 survivors throughout the disease crisis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
78
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(101 citation statements)
references
References 23 publications
(27 reference statements)
6
78
0
4
Order By: Relevance
“…Studies above identified COVID-19 survivors at high risk for psychological problems. Good social support and a number of simple attitudes or activities should be done to prevent psychiatric sequelae in COVID-19 survivors, such as strengthen bonds with other people through social media, think and talk positively, sleep properly, balance diet, regular daily routine, relaxation exercise and other healthy lifestyle measures[ 49 , 55 ]. Music therapy can also be a relevant and simple strategy to improve mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Studies above identified COVID-19 survivors at high risk for psychological problems. Good social support and a number of simple attitudes or activities should be done to prevent psychiatric sequelae in COVID-19 survivors, such as strengthen bonds with other people through social media, think and talk positively, sleep properly, balance diet, regular daily routine, relaxation exercise and other healthy lifestyle measures[ 49 , 55 ]. Music therapy can also be a relevant and simple strategy to improve mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that psychological sequelae are an important issue among COVID-19 survivors. 7 , 9 11 In the USA, survivors of COVID-19 have been found to experience psychiatric disorders 14–90 days after a COVID-19 diagnosis, and anxiety disorders, insomnia and dementia were mostly observed. 10 In South Korea, the development of psychological sequelae has been recently reported in COVID-19 survivors.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Psychological sequelae has been reported as an important issue in current literature. 7 9 In a previous cohort study from the USA, survivors of the diseases who had no previous psychiatric history had a higher risk of developing psychiatric disorders during the 14–90 days follow-up period. 10 In South Korea, a high association of psychological sequelae in COVID-19 survivors has been reported in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Studies focusing on the psychological experience of patients with COVID-19 are relatively fewer, especially during the period of hospitalization. As informed by qualitative research, patients reported their experience as “living in limbo” and because of the high mortality and uncertainty about the prognosis, participants were trapped between life and death ( 13 ). Therefore, the pressure of survival threat is an important psychological stressor for inpatients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%